Preparation and preclinical evaluation of a 68Ga-labelled c(RGDfK) conjugate comprising the bifunctional chelator NODIA-Me - Tilman Läppchen; Jason P. Holland; Yvonne Kiefer; Mark D. Bartholomä (SpringerOpen, 2018)
Abstract Background We recently developed a chelating platform based on the macrocycle 1,4,7-triazacyclononane with up to three, five-membered azaheterocyclic arms for the development of 68Ga- and 64Cu-based radiopharmaceuticals. Here, a 68Ga-labelled conjugate comprising the bifunctional chelator NODIA-Me in combination with the αvß3-targeting peptide c(RGDfK) has been synthesized and characterized. The primary aim was to evaluate further the potential of our NODIA-Me chelating system for the development of 68Ga-labelled radiotracers. Results The BFC NODIA-Me was conjugated to c(RGDfK) by standard peptide chemistry to obtain the final bioconjugate NODIA-Me-c(RGDfK) 3 in 72% yield. Labelling with [68Ga]GaCl3 was accomplished in a fully automated, cGMP compliant process to give [68Ga]3 in high radiochemical yield (98%) and moderate specific activity (~ 8 MBq nmol− 1). Incorporation of the Ga-NODIA-Me chelate to c(RGDfK) 2 had only minimal influence on the affinity to integrin αvß3 (IC50 values [natGa]3 = 205.1 ± 1.4 nM, c(RGDfK) 2 = 159.5 ± 1.3 nM) as determined in competitive cell binding experiments in U-87 MG cell line. In small-animal PET imaging and ex vivo biodistribution studies, the radiotracer [68Ga]3 showed low uptake in non-target organs and specific tumor uptake in U-87 MG tumors. Conclusion The results suggest that the bifunctional chelator NODIA-Me is an interesting alternative to existing ligands for the development of 68Ga-labelled radiopharmaceuticals.